2017
DOI: 10.4103/ijo.ijo_730_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of endothelial cell loss following phacoemulsification in pupils of different sizes

Abstract: Purpose:To compare Endothelial cell(EC) loss following Phacoemulsification (PKE) in pupils of different sizes.Methods:A prospective double masked observational study in which a total of 150 eyes of 150 patients between 50 & 70 years of age with senile cataract of nuclear sclerosis grade II were enrolled. Patients were allocated into three groups of 50 eyes each in Group A (pupil size <5 mm), Group B (pupil size 5–7 mm) and Group C (pupil size >7 mm). Pupillary size was measured by determining the height of sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…During cataract surgery, endothelial cell loss may be caused by ultrasound vibration, air bubbles, turbulent flow of irrigating solution, direct contact with surgical instruments, or the IOL during the surgical procedure. 8,104…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During cataract surgery, endothelial cell loss may be caused by ultrasound vibration, air bubbles, turbulent flow of irrigating solution, direct contact with surgical instruments, or the IOL during the surgical procedure. 8,104…”
Section: Resultsmentioning
confidence: 99%
“…During cataract surgery, endothelial cell loss may be caused by ultrasound vibration, air bubbles, turbulent flow of irrigating solution, direct contact with surgical instruments, or the IOL during the surgical procedure. 8,104 Several studies of SF IOL implantation (both sutured and sutureless) have reported an average 2.1% to 6% endothelial cell loss postoperatively. 23,27,41,42,51,63 In addition, there are reports of endothelial cell loss of up to 14.1% after 3 months, 17.5% after 7 months, and 27% after 1 year of SF IOL implantation.…”
Section: Endothelial Cell Lossmentioning
confidence: 99%
“…22 Corneal endothelial cell density is reduced by ∼0.5% per year with normal aging, and additional endothelial cell loss can occur after cataract surgery. [28][29][30] Previous in vitro studies demonstrated the formation of cavitation bubbles at the probe tip that was dependent on the ultrasound power. 15,22,31 An in vitro phacoemulsification study that simulated cataract surgery reported the formation of free radicals, generated as a result of acoustic cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery is the most commonly performed ophthalmic procedure worldwide. Although phacoemulsification is effective in providing good visual acuity, the dissipation of ultrasonic energy during phacoemulsification causes mechanical and thermal damage to the corneal endothelium [ 1 ]. Corneal endothelial cells play a pivotal role in maintaining corneal transparency; therefore, damage to corneal endothelium function may lead to corneal edema and, in advanced stages, corneal decompensation/bullous keratopathy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%